Rancang Bangun Sistem Informasi Usaha Amori Florist Berbasis Smartphone Android dengan Menerapkan Supply Chain Management - Muhammad Budi Nur Ihsan (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Android smartphone is one of the devices that is difficult to escape from the human grip in today's era. With the large number of Android smartphone users, various kinds of software/applications based on Android smartphones are increasingly popping up. One of the ideas that can be applied in making android smartphone-based applications is an information system application for businesses or shops by implementing supply chain management (SCM). SCM itself is a series of supply chain management activities that are implemented and integrated to plan, control, and run the product flow including processes such as management of raw materials, production processes, until the product reaches the end consumer in an effective and efficient manner. Amori Florist is a wreath board business located in the city of Palembang, precisely in the Plaju Lorong Banten 2 area of ​​Palembang city. The system to be built is an information system for the management of goods data, orders, order transfers, and so on with the aim of reducing wasted time, maximizing employee performance, including consumers. With the application of this information system, it is hoped that it will provide convenience for Amori florist in running their business Keywords— Supply Chain Management, Amori Florist, Android App